Quality of Government and Living Standards - Grigoli, Francesco; Ley, Eduardo (World Bank, Washington, DC, 2014)
It is generally acknowledged that a government's output is difficult to define and its value is hard to measure. The practical solution adopted by national accounts systems is to equate output value to input costs, but well-documented inefficiencies in government activities make this approximation questionable. One solution is to purge from gross domestic product (GDP) the fraction of government inputs that is wasted. This note illustrates such a correction, computing corrected per capita GDP on the basis of two studies that estimate efficiency scores for several dimensions of government activities. Results show that the correction could be significant and reorder the rankings of living standards.